Workshop 3 report: Market initiative regimes in bus, coach and rail: Recent developments, threats, developing paradigms and regulatory needs. (September 2018) - van de Velde, Didier; Karl, Astrid
Abstract: This paper synthesizes evidence from Workshop 3 'Market initiative regimes: experience and measures to improve performance' of the 15th International Conference on Competition and Ownership in Land Passenger Transport. This workshop discussed the growing importance of market initiative regimes in public transport focussing on the market and regulatory developments in three sectors: local and regional bus, long-distance coach and passenger train services. The comparison of these sectors illustrated impressive but also very substantial differences between countries in terms of market potentials, success of market initiative, regulatory paths taken and resulting performance. Various observations were made. The size and stratification of passenger transports markets in most countries or regions studied seemed to leave little room for direct intramodal competition, while there was more trust in the viability of intermodal competition. The lack of data was perceived to be a major issue, not only for research but also for market transparency and well-functioning. The development of new intermediaries for information and ticketing purposes seems to point at a possible gradual replacement of the 'old' public transport integration dogma with some new paradigm. There is still a lack of academic studies focussing on the process leading to demand and supply of regulation of market initiative regimes and of studies looking subsequently at the factors leading to the uptake of such regulatory tools or at the practical requirements for such specific regulations to function.